Toward environmentally-benign utilization of nonmetallic fraction of waste printed circuit boards as modifier and precursor. (January 2015) - Hadi, Pejman; Ning, Chao; Ouyang, Weiyi; Xu, Meng; Lin, Carol S.K.; McKay, Gordon
Highlights: Environmental impacts of electronic waste and specifically waste printed circuit boards. Review of the recycling techniques of waste printed circuit boards. Advantages of physico-mechanical recycling techniques over chemical methods. Utilization of nonmetallic fraction of waste printed circuit boards as modifier/filler. Recent advances in the use of nonmetallic fraction of waste printed circuit boards as precursor. Abstract: Electronic waste, including printed circuit boards, is growing at an alarming rate due to the accelerated technological progress and the shorter lifespan of the electronic equipment. In the past decades, due to the lack of proper economic and environmentally-benign recycling technologies, a major fraction of e-waste generated was either destined to landfills or incinerated with the sole intention of its disposal disregarding the toxic nature of this waste. Recently, with the increasing public awareness over their environment and health issues and with the enaction of more stringent regulations, environmentally-benign recycling has been driven to be an alternative option partially replacing the traditional eco-unfriendly disposal methods. One of the most favorable green technologies has been the mechanical separation of the metallic and nonmetallic fraction of the waste printed circuit boards. Although metallic fraction, as the most profitable component, is used to generate the revenue of the separation process, the nonmetallic fraction (NMF) has been left isolated. Herein, the recent developments in the application of NMF have been comprehensively reviewed and an eco-friendly emerging usage of NMF as a value-added material for sustainable remediation has been introduced.